Ocellatin peptides from the skin secretion of the South American frog Leptodactylus labyrinthicus (Leptodactylidae): characterization, antimicrobial activities and membrane interactions. Issue 1 (December 2017) - Gusmão, Karla; dos Santos, Daniel; Santos, Virgílio; Cortés, María; Reis, Pablo; Santos, Vera; Piló-Veloso, Dorila; Verly, Rodrigo; de Lima, Maria; Resende, Jarbas
Abstract Background The availability of antimicrobial peptides from several different natural sources has opened an avenue for the discovery of new biologically active molecules. To the best of our knowledge, only two peptides isolated from the frogLeptodactylus labyrinthicus, namely pentadactylin and ocellatin-F1, have shown antimicrobial activities. Therefore, in order to explore the antimicrobial potential of this species, we have investigated the biological activities and membrane interactions of three peptides isolated from the anuran skin secretion. Methods Three peptide primary structures were determined by automated Edman degradation. These sequences were prepared by solid-phase synthesis and submitted to activity assays against gram-positive and gram-negative bacteria and against two fungal strains. The hemolytic properties of the peptides were also investigated in assays with rabbit blood erythrocytes. The conformational preferences of the peptides and their membrane interactions have been investigated by circular dichroism spectroscopy and liposome dye release assays. Results The amino acid compositions of three ocellatins were determined and the sequences exhibit 100% homology for the first 22 residues (ocellatin-LB1 sequence). Ocellatin-LB2 carries an extra Asn residue and ocellatin-F1 extra Asn-Lys-Leu residues at C-terminus. Ocellatin-F1 presents a stronger antibiotic potential and a broader spectrum of activities compared to the other peptides. The membrane interactions and pore formation capacities of the peptides correlate directly with their antimicrobial activities, i.e., ocellatin-F1 > ocellatin-LB1 > ocellatin-LB2. All peptides acquire high helical contents in membrane environments. However, ocellatin-F1 shows in average stronger helical propensities. Conclusions The obtained results indicate that the three extra amino acid residues at the ocellatin-F1 C-terminus play an important role in promoting stronger peptide-membrane interactions and antimicrobial properties. The extra Asn-23 residue present in ocellatin-LB2 sequence seems to decrease its antimicrobial potential and the strength of the peptide-membrane interactions.